2015
DOI: 10.1016/j.rchipe.2015.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Asociación entre los niveles de zinc intracelular y el estado nutricional de los niños infectados por el virus de la inmunodeficiencia humana (VIH) y los niños expuestos al virus no infectados

Abstract: The deterioration of nutritional status and growth retardation in children were associated with HIV, but not with the levels of intracellular zinc. The dietary intake of this nutrient was not associated with levels of zinc in monocytes or CD4 + and CD4- lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(16 reference statements)
1
2
0
1
Order By: Relevance
“…The findings of this study also showed that HIV-infected children on ART had greater CD4 counts and were less likely of being underweight and wasted, which contributing to better health status and less hospitalization. Consistent with the previous studies, ART exerted a favorable effect on growth [ 2 , 6 , 32 ] and immune functions. [ 35 ]…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of this study also showed that HIV-infected children on ART had greater CD4 counts and were less likely of being underweight and wasted, which contributing to better health status and less hospitalization. Consistent with the previous studies, ART exerted a favorable effect on growth [ 2 , 6 , 32 ] and immune functions. [ 35 ]…”
Section: Discussionsupporting
confidence: 90%
“…[ 27 – 31 ] A previous study confirmed that growth retardation and the deterioration of nutritional status in children were associated with HIV infection. [ 32 ] The previous studies in South Africa and Tanzania demonstrated that HIV infection was associated with an increased burden of child underweight and wasting, [ 33 ] even among ART-treated children. [ 11 ] Infection with HIV causes immune impairment and further leads to malnutrition that could contribute to increased mortality in children.…”
Section: Discussionmentioning
confidence: 99%
“…This is like that reported age in Central and Western Africa (Chad, Cameroon, Mali, Ivory Coast, Togo, Benin) [ 17 ] but higher than that reported by studies in Nigeria and southern India [ 18 , 19 ]. A previous study confirmed that stunting and nutritional status deterioration in children were associated with HIV infection [ 20 ]. The late diagnosis of HIV infection, with resultant significant immunodeficiency, the duration of the disease, and inadequate nutrition are factors associated with chronic malnutrition [ 15 , 19 - 21 ].…”
Section: Discussionmentioning
confidence: 55%
“…Asimismo, en países asiáticos la prevalencia de desnutrición global en población pediátrica con VIH oscila entre 17-63% (9,16) . Con respecto al diagnóstico de desnutrición crónica, similares resultados se reportaron para pacientes con VIH de 15 meses a 19 años (9,(17)(18)(19) . Otros estudios epidemiológicos documentaron mayor prevalencia de desnutrición crónica (2,16,20,21) observando el retraso del crecimiento lineal en niños mayores de 9, probablemente debido a la progresión de la enfermedad (16,21) .…”
Section: Discussionunclassified